KONDISI SOSIAL EKONOMI DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI PADI DI KECAMATAN TRIMURJO KABUPATEN LAMPUNG TENGAH - Salsabilla, Cahaya; Zakaria, Wan Abbas; Marlina, Lina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
This research aims to analyze the socio-economic conditions and the welfare level of paddy farmer households. The research location was purposely determined in Trimurjo Subdistrict, Central Lampung Regency. The research locations were determined using the Proportionate Stratified Random Sampling method, which divides the population into several categories based on land size. The number of samples in this study was 70 farmers taken from 2 villages, namely Tempuran Village with 47 people and Pujodadi Village with 23 people. The data analysis method for the socio-economic study was analyzed using descriptive quantitative methods. The welfare level was measured using the poverty line method of BPS (2024), World Bank (2023), and good service ratio (GSR). The results of the study indicate that the socio-economic conditions of paddy farmer households are dominated by farmers with an average age of 56 years, who have completed senior high school or its equivalent, and have side jobs as livestock breeders. Based on the BPS (2024) and the World Bank (2023) welfare level, farming households are classified as prosperous as their expenditure is above the minimum welfare threshold, which is IDR 3,024,817 per month or IDR 100,827 per day. However, according to the Good Service Ratio (GSR) method, the farmers are classified as less prosperous as the GSR value is greater than 1. Key words: farmer households, socio-economic, welfare